APPROACHES TO THE CHOICE OF ANTICOAGULANT THERAPY IN THE TREATMENT OF PATIENTS WITH COMBINATION OF ATRIAL FIBRILLATION WITH CORONARY HEART DISEASE OR PERIPHERAL ATHEROSCLEROSIS: POTENTIAL OF APIXABAN - O. D. Ostroumova; A. I. Kochetkov; I. Yu. Orlova; E. A. Smolyarchuk; J. S. Pavlova (Столичная издательская компания, 2018)
The choice of anticoagulant therapy in patients with atrial fibrillation (AF) and concomitant diseases - coronary heart disease (CHD), including acute coronary syndrome (ACS) in history, peripheral arterial disease (PAD), is discussed in the article. The overall mortality and incidence of myocardial infarction in patients with CHD and AF is higher than in patients with AF without CHD. Patients with AF and PAD compared to patients with AF without PAD have higher risks both stroke and systemic embolism. The prescription of triple antithrombotic therapy is necessary for patients with a combination of AF and CHD who underwent percutaneous coronary interventions (in ACS or elective surgery). The possibility of prescription and duration, the choice of specific drugs and their doses should be determined individually, based on the risks of ischemic events associated with stenting, the risk of ischemic stroke and bleeding. Use of new oral anticoagulants (NOAC) instead of vitamin K antagonists (eg, warfarin), low doses of NOAC, studied in trials and proven efficacy in the prevention of stroke/systemic embolism, the use of clopidogrel as a drug of choice from the P2Y12 inhibitor group, the use of low doses of acetylsalicylic acid (ASA), the routine administration of drugs from the proton pump inhibitor group is recommended to minimize the risk of bleeding. The data of subanalysis of the ARISTOTEL randomized clinical trial, indicating a high profile of efficacy and safety of apixaban in patients with AF, depending on the presence of CHD, PAD, concomitant use of ASA, are also presented in the article. The benefits of apixaban over warfarin for reducing the risk of stroke/systemic embolism, total mortality and the risk of bleeding in a subgroup of CHD patients are just as obvious as in the general population of the ARISTOTLE study, and in the subgroup of patients without CHD. Treatment with apixaban, both in the subgroup of patients taking ASA, and a subgroup of patients without ASA, is accompanied by a lower risk of strokes and systemic embolism and a lower incidence of major bleeding. The risk of stroke or systemic embolism was similar in patients with AF and PAD randomized to the apixaban group or to the warfarin group, as well as in patients with AF without PAD. Patients with AF and PAD who received apixaban or warfarin had a similar incidence of major bleeding or clinically significant minor bleeding.